The Distribution Model of Fashion Products in Social Commerce: Brand Loyalty and Purchase Decisions - Sudirman, Acai; Setiyawami, Setiyawami; Setyawati, Christina Yanita (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study examines the influence of influencer marketing, electronic word of mouth (e-WOM), and perceived value on brand loyalty and purchase decisions within the digital bazaar of fashion-oriented social commerce. By interrogating the interplay of virtual persuasion and consumer allegiance, it offers a nuanced reading of how contemporary loyalty is forged not in brand temples, but in communal whispers. Utilizing a quantitative survey of active online fashion consumers and analyzed through Structural Equation Modeling, the findings reveal that while e-WOM and perceived value foster loyalty, influencer marketing does not. Conversely, influencer marketing and e-WOM sway purchase decisions, yet perceived value proves impotent in this regard. These findings upend the influencer-as-oracle myth and suggest that brand managers might do well to invest not merely in charisma, but in cultivating credible digital communities that whisper trust louder than slogans.